2004
DOI: 10.1128/aac.48.6.1974-1982.2004
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of Moxifloxacin on Activated Human Monocytic Cells: Inhibition of NF-κB and Mitogen-Activated Protein Kinase Activation and of Synthesis of Proinflammatory Cytokines

Abstract: We previously showed that moxifloxacin (MXF) exerts protective anti-inflammatory effects in immunosup-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
61
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(68 citation statements)
references
References 48 publications
5
61
2
Order By: Relevance
“…The inhibitory effect of MXF on cytokine secretion from THP-1 cells also confirms our previous observations of MXF inhibition of the synthesis of proinflammatory cytokines in THP-1 cells and human peripheral blood monocytes stimulated with LPS-phorbol myristate acetate (Weiss et al, 2004) or Aspergillus fumigatus (Shalit et al, 2006). Additionally, MXF inhibited NF-kB and mitogen-activated protein kinase activation in THP-1 cells and in a human respiratory epithelial cell line (Weiss et al, 2004;Werber et al, 2005).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The inhibitory effect of MXF on cytokine secretion from THP-1 cells also confirms our previous observations of MXF inhibition of the synthesis of proinflammatory cytokines in THP-1 cells and human peripheral blood monocytes stimulated with LPS-phorbol myristate acetate (Weiss et al, 2004) or Aspergillus fumigatus (Shalit et al, 2006). Additionally, MXF inhibited NF-kB and mitogen-activated protein kinase activation in THP-1 cells and in a human respiratory epithelial cell line (Weiss et al, 2004;Werber et al, 2005).…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, MXF inhibited NF-kB and mitogen-activated protein kinase activation in THP-1 cells and in a human respiratory epithelial cell line (Weiss et al, 2004;Werber et al, 2005). Using a murine model of Candida pneumonia in immune-suppressed animals, we found that MXF exerted a protective anti-inflammatory effect, resulting in a marked decrease in bronchopneumonia and enhanced survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations confirm our previous studies that demonstrated significant inhibition by MXF of the synthesis of proinflammatory cytokines in THP-1 cells and in human peripheral blood monocytes stimulated with LPS-phorbol myristate acetate (37) or Aspergillus fumigatus (38). The combined effect of MXF on inhibition of VP-16-induced IL-8 and of spontaneous secretion of VEGF from HT-29 cells may be an important aspect of MXF activity.…”
Section: Discussionsupporting
confidence: 91%
“…ciprofloxacin or moxifloxacin may exert anti-inflammatory effects besides their well-established antimicrobial properties, as suggested by various in vitro studies [55][56][57][58]. However, in an experimental pneumonia model comparing moxifloxacin with the standard regimen of β-lactam therapy, no such effect could be detected [59].…”
Section: Beyond Bacterial Killing: Immunomodulating Effects Of Antibimentioning
confidence: 99%